Logical Operators for the Data-oriented Design of the User Interfaces. (2015) - Muji, Marius
Abstract: Currently, user interface development involves procedural technologies, being both time-consuming and error-prone. This paper proposes a logical data model as a theoretical foundation for declarative technologies capable to reduce the development time, to eliminate human errors, and to raise the level of abstraction at which the information system is designed. The paper provides formal definitions for the model‟s data structures and for its specific operators, and concludes with some important applications.